Inclusive development, translation, and Indigenous-language pop: Yoku Walis’s Seejiq hip hop - Sterk, Darryl Cameron (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2022)
This article is about a cost-effective approach to inclusive development in a settler state that shows what translation has to offer minorities. For almost two decades, Taiwan’s government has rewarded Indigenous minority recording artists who sing in endangered ancestral languages at the Golden Melody Awards (GMAs), Taiwan’s Grammys. These language-based GMAs stimulate the private production of popular music in such languages. They also stimulate translation into such languages, which certain recording artists have been learning as adults. I found that one GMA hopeful, Yoku Walis, translated her hip-hop lyrics from Mandarin Chinese into Seejiq, her ancestral language, with a language learner in mind, and that a pedagogical goal also guided the titling of her music videos. But language pedagogy is only one part of an innovative package. Yoku’s Seejiq hip hop is a contribution to inclusive linguistic and cultural development. The language-based GMAs illustrate the ways in which settler states such as Taiwan can help to empower Indigenous translators such as Yoku to make such contributions.